Pharmacokinetic-Pharmacodynamic Evaluation of Gepotidacin against Gram-Positive Organisms Using Data from Murine Infection Models - Bulik, Catharine C. (Antimicrob Agents Chemother, 2017)
Gepotidacin (formerly called GSK2140944) is a novel triazaacenaphthylene bacterial topoisomerase inhibitor with in vitro activity against conventional and biothreat pathogens, including Staphylococcus aureus and Streptococcus pneumoniae. Using neutropenic murine thigh and lung infection models, the pharmacokinetics-pharmacodynamics (PK-PD) of gepotidacin against S. aureus and S. pneumoniae were characterized. Candidate models were fit to single-dose PK data from uninfected mice (for doses of 16 to 128 mg/kg of body weight given subcutaneously [s.c.]). Dose fractionation studies (1 isolate/organism; 2 to 512 mg/kg/day) and dose-ranging studies (5 isolates/organism; 2 to 2,048 mg/kg/day; MIC ranges of 0.5 to 2 mg/liter for S. aureus and 0.125 to 1 mg/liter for S. pneumoniae) were conducted. The presence of an in vivo postantibiotic effect (PAE) was also evaluated. Relationships between the change from baseline in log(10) CFU at 24 h and the ratio of the free-drug plasma area under the concentration-time curve (AUC) to the MIC (AUC/MIC ratio), the ratio of the maximum concentration of drug in plasma (C(max)) to the MIC (C(max)/MIC ratio), and the percentage of a 24-h period that the drug concentration exceeded the MIC (%T>MIC) were evaluated using Hill-type models. Plasma and epithelial lining fluid (ELF) PK data were best fit by a four-compartment model with linear distributional clearances, a capacity-limited clearance, and a first-order absorption rate. The ELF penetration ratio in uninfected mice was 0.65. Since the growth of both organisms was poor in the murine lung infection model, lung efficacy data were not reported. As determined using the murine thigh infection model, the free-drug plasma AUC/MIC ratio was the PK-PD index most closely associated with efficacy (r(2) = 0.936 and 0.897 for S. aureus and S. pneumoniae, respectively). Median free-drug plasma AUC/MIC ratios of 13.4 and 58.9 for S. aureus, and 7.86 and 16.9 for S. pneumoniae, were associated with net bacterial stasis and a 1-log(10) CFU reduction from baseline, respectively. Dose-independent PAE durations of 3.07 to 12.5 h and 5.25 to 8.46 h were demonstrated for S. aureus and S. pneumoniae, respectively.